Evaluation of the efficacy of Guided Tissue Regeneration in deep bone defects of single-rooted teeth classified as “hopeless” - Wiench, Rafał; Gilowski, Łukasz; Kulczycka, Justyna; Domka, Wojciech; Jabłoński, Przemysław (Journal of Stomatology, 2017)
Objectives: Evaluation of the efficacy of GTR in deep bone defects with single-root teeth classified as hopeless. Material and Methods: The study involved 16 patients (18 hopeless teeth). Before treatment, after 6 and 12 months clinical attachment level (CAL), probing depth (PD), as well as depth of bone loss as a percentage of root height were evaluated. GTR procedures were performed using bone substitute material and resorbable barrier membranes. Result: Three patients required a tooth extraction within one year of the procedure. In the remaining patients, mean value of CAL parameter decreased from 14.1 mm to 8.4 mm (p <0.05), PD from 12.5 mm to 4.2 mm one year after the treatment (p <0.05). Before the treatment, bone defect was 93% (73% - 121%) of root length on average. After the treatment, the same parameter equaled 57% (27% -78%) (p <0.05). In four patients (4/13), bone loss was reduced to less than 50% (27% -47%) in the X-ray, while in the remaining patients (9/13) bone loss was still above 50% (58% -78%) one year after the treatment. Conclusion: GBR is an effective treatment for even very deep vertical bone defects with single-root teeth, which can change the initial evaluation of the „hopeless” tooth prognosis.